Trade-off between crop and livestock production and evolution of mixed farming in West African moist savanna - Jabbar, M.A.; Okoruwa, V.; Akinwumi, J.A. (South African Society of Animal Science, 1996)
In West Africa, crop-livestock mixed farming is emerging from the currently predominant nomadic pastoralism and agropastoralism. It is hypothesized that competitiveness between crop and livestock enterprises may be an important determinant of the pace of this evolution. A field study in the derived savanna of Southwest Nigeria shows that at the current stage of evolution, as a crop farmer adds livestock to his business, there is a small gain in the beginning, then an increasing rate of substitution between crop and livestock follow. As a livestock rearer engages in crop production, there is a decreasing rate of subsitution between livestock and crop. This situation derives from the fact that crop production is more intensive than llivestock production which depends principally on grazing natural pastures. Results indicate that, if increased population pressure and cropping intensity severely limit access to grazing land, farm and herds sizes will become smaller, then the degree of integration between crop and livestock will increase significantly.